2000
DOI: 10.1111/0022-4537.00176
|View full text |Cite
|
Sign up to set email alerts
|

New Trends in Measuring Environmental Attitudes: Measuring Endorsement of the New Ecological Paradigm: A Revised NEP Scale

Abstract: Dunlap and Van Liere's New Environmental Paradigm (NEP) Scale, published in 1978, has become a widely used measure of proenvironmental orientation. This article develops a revised NEP Scale designed to improve upon the original one in several respects: (1) It taps a wider range of facets of an ecological worldview, (2) It offers a balanced set of pro-and anti-NEP items, and (3) It avoids outmoded terminology. The new scale, termed the New Ecological Paradigm Scale, consists of 15 items. Results of a 1990 Washi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

111
3,763
20
282

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 4,366 publications
(4,176 citation statements)
references
References 45 publications
111
3,763
20
282
Order By: Relevance
“…The high degree of internal consistency among the five NEP-items suggests that it is appropriate to combine them into a single measure of environmental attitudes. These results are consistent with several studies that have also found it expedient to represent the NEP-items by a single dimension (e.g., Dunlap et al, 2000).…”
Section: Environmental Attitudessupporting
confidence: 92%
See 2 more Smart Citations
“…The high degree of internal consistency among the five NEP-items suggests that it is appropriate to combine them into a single measure of environmental attitudes. These results are consistent with several studies that have also found it expedient to represent the NEP-items by a single dimension (e.g., Dunlap et al, 2000).…”
Section: Environmental Attitudessupporting
confidence: 92%
“…Previous studies have consistently found that environmentalists score higher on the NEP-scale than the general public (e.g., Dunlap et al, 2000).…”
Section: Environmental Attitudesmentioning
confidence: 92%
See 1 more Smart Citation
“…It is further characterized by high convergent validity between verbal commitment and affect since both sub-scales show distinct correlative patterns which is in line with our definition. ddAn example from the policy approach shown in Table 3 is the most widely used 'New Environmental Paradigm Scale' (NEP) (Dunlap and Van Liere, 1978) and also its revised version, the 'New Ecological Paradigm' measure (Dunlap, van Liere, Mertig and Jones , 2000). It includes the sub-scales on a 'humans' ability to upset the balance of nature, existence of limits of growth' and 'humans' right to rule over the rest of nature'.…”
Section: Evaluation Of Scales and Measuresmentioning
confidence: 99%
“…b (*) p < 0.05; (**) p < 0.01; (***) p < 0.001. Section 7 of the survey addressed general environmental issues, using Dunlap et al's 15-item New Ecological Paradigm Scale (NEPS) (19). Section 8 asked for demographic information such as age, gender, and education level.…”
Section: Design Of Studymentioning
confidence: 99%